Rhythms of the Afro-Atlantic World Rituals and Remembrances - Diouf, Mamadou; Nwankwo, Ifeoma Kiddoe (University of Michigan Press, 2010)
Along with linked modes of religiosity, music and dance have long occupied a central position in the ways in which Atlantic peoples have enacted, made sense of, and responded to their encounters with each other. This unique collection of essays connects nations from across the Atlantic---Senegal, Kenya, Trinidad, Cuba, Brazil, and the United States, among others---highlighting contemporary popular, folkloric, and religious music and dance. By tracking the continuous reframing, revision, and erasure of aural, oral, and corporeal traces, the contributors to Rhythms of the Afro-Atlantic World collectively argue that music and dance are the living evidence of a constant (re)composition and (re)mixing of local sounds and gestures.